Carbon Nanotubes: Atomistic Investigation of Load Transfer Between DWNT Bundles "Crosslinked" by PMMA Oligomers (Adv. Funct. Mater. 15/2013). (14th April 2013) - Naraghi, Mohammad; Bratzel, Graham H.; Filleter, Tobin; An, Zhi; Wei, Xiaoding; Nguyen, SonBinh T.; Buehler, Markus J.; Espinosa, Horacio D.
<x xml:space="preserve">Abstract</x> On page 1883 Markus J. Buehler, Horacio D. Espinosa, and co‐workers report a study designed to probe the interfacial shear strength between carbon nanotube (CNT) bundles, which is a key element in the bottom‐up hierarchical design of CNT fibers with unprecedented mechanical performance. The back cover image blends renderings from atomistic and coarse‐grain molecular dynamics simulations with scanning electron microscopy images of shearing between surface‐functionalized doublewalled nanotube (DWNT) bundles. The background shows a mat of CNT bundles from which a pair of bundles is selected for testing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>